Heterotopic sebaceous glands in the esophagus, a very rare histopathological diagnosis: a case report and review of the literature. Issue 2 (29th December 2016) - Montalvo, Nelson; Tapia, Verónica; Padilla, Hernán; Redrobán, Ligia
Key Clinical Message: Sebaceous glands are very rarely found in the esophagus. Existing reports do not contain sufficient epidemiological, etiological, clinical, or prognostic data. Its histogenesis suggests heterotopia or metaplasia. Despite its extreme rarity, correct and generally easy identification enables establishing the proper patient monitoring. Abstract : Sebaceous glands are very rarely found in the esophagus. Existing reports do not contain sufficient epidemiological, etiological, clinical, or prognostic data. Its histogenesis suggests heterotopia or metaplasia. Despite its extreme rarity, correct and generally easy identification enables establishing the proper patient monitoring.